Multiple slip, Soret and Dufour effects in fluid flow near a vertical stretching sheet in the presence of magnetic nanoparticles - Eleni Seid; Eshetu Haile; Tadesse Walelign (International Journal of Thermofluids, 2022)
This paper presents a mathematical analysis of multiple slip, Soret and Dufour effects in a boundary layer flow of an electrically conducting nanofluid over a vertically stretching sheet. The flow situation has been described mathematically by using partial differential equations. Suitable transformations are utilized to make the model equation convenient for computation. An efficient optimal homotopy analysis method has been implemented successfully to obtain analytic approximations to the unknown functions in the flow problem. The influences of wall slip parameters, porosity of the medium, Buoyancy forces, magnetic field, thermal radiation, Soret and Dufour effects, heat source and chemical reaction parameters are examined in detail. The variations of the dimensionless velocity, temperature and concentration profiles in relation to the emerging parameters are explored intensively. The rates of momentum, heat and mass transfer near the stretching surface are also studied against the pertinent parameters. The study reveals that the increase in velocity slip parameter speeds up the fluid motion and increasing the Soret effect raises concentration of nanoparticles near the stretching sheet. Further, the analytic approximations for the solutions of the present model obtained by implementing the optimal homotopy analysis method are found in a very good agreement with some early works under common assumptions.